Materiais com terminologia das Ciências Biológicas em língua brasileira de sinais (Libras): suas estruturas e potencialidades didáticas - Fontes, Gisele de Souza (2023)
In recent years, there has been an increase in the production of lexicographical and terminological materials in Brazilian Sign Language (Libras) containing terms from the field of Biological Sciences. Such materials assist teachers, translators, interpreters, as well as deaf and hearing students involved in this knowledge area. Thus, with this documentary work, the aim is to analyze materials containing terminology from Biological Sciences in Libras. To achieve this goal, the dissertation draws on theoretical foundations articulated by two sets of authors: those discussing bilingual education for the deaf and those discussing lexicographical and terminological materials, especially in Libras and Portuguese. Therefore, an analysis was conducted on a set of 10 materials known to the author, published between 2005 and 2021, and containing terminology related to Biological Sciences in Libras, including books, glossaries, dictionaries, manuals, guides, and others. The analysis proceeded according to the structure and organization of each material, whether in Portuguese or Libras, in physical or digital form. Each material presented something in common (a sign in Libras, a word, phrase, or short text in Portuguese, and a real or illustrated image of what is being represented in Libras), and some showed differences in structure (sign writing, terms in English, video of the sign in Libras trough QR Code, link directing to videos with images, texts in Spanish, written and vocal Portuguese texts). Overall, the terms with the highest occurrence are related to the following disciplines: Botany, Anatomy, and Human Physiology. It is noteworthy that, for the most part, the analyzed documents were not entirely bilingual. It is considered that the materials have didactic potential as they record Biological Sciences terms in Libras, providing knowledge of specialized lexicon for speakers of this language. The research is understood to offer contributions to discussions about the production and use of terminological materials in Libras and Portuguese for consultants involved with these languages.